Definitions of localized energy states on the quasi-fermi level with changing times - Guliamov, G.; Sharibaev, N.Y.; Erkaboev, U.I. (Физическая инженерия поверхности, 2013)
Studies of the generation-recombination process of electrons from the filled localized surface states at the time of their lives. The applicability of the derivative of the Dirac distribution as δ-function at low temperatures in order to study the temperature dependence of the spectrum of the density of surface states. To improve the accuracy of the results in the paper, a method of discrete states spectroscopy on quasi-Fermi level with the changing times.